Why a pregnant age can be the risk factor in chronic obstructive pyelonephritis? - E. F. Barinov; Kh. V. Grigoryan; A. O. Balykina; T. I. Faber (Kazimierz Wielki University, 2017)
The aim of the study was to identify possible mechanisms that could reproduce the recurrence of CVD in older men against the background of non-steroidal anti-inflammatory drugs and antibiotics, thereby justifying why age and sex may be risk factors for acute pyelonephritis in urolithiasis. Material and methods. The results of a study of 88 men with chronic obstructive pulmonary disease, including 45 patients over 65 years of age (mean age 74.0 ± 1.3 years) and 43 patients in the age range of 55-65 years (mean age of patients 61.0 ± 0, 8 year). In the phase of remission of CVD, 48 patients were examined and in the phase of relapse-40 patients. The study included patients who took non-steroidal anti-inflammatory drugs (NSAIDs) and antibiotics in a standard dose of at least 5-10 days before hospitalization. From the peripheral blood by centrifugation, plasma-enriched plasma was isolated. Platelet content in 1 μl was 200,000 ± 20,000. To stimulate platelets, adrenaline and ADP (Sigma, USA) were used at an effective concentration (EC50) of 5 μM, which caused platelet aggregation (ATC) in healthy individuals (10 donors) at the level of 50 ± 5%. The aggregation of Tc was evaluated on a Chrono log analyzer (USA). The formation of platelet-leukocyte aggregates (TPA) was modeled in vitro by incubation of stimulated platelets (epinephrine at a concentration of EC50) and intact leukocytes isolated from the peripheral blood of patients with CVD. The number of intact TL was assessed after the color of blood smears according to the Romanovsky-Giemsa method. Results. In the phase of remission of CVD on the background of the appointment of NSAIDs and antibiotics, in patients of the two age groups studied, it was not possible to detect differences in the response of leukocytes. Recurrence of CVD in patients age range 55-65 years was characterized by leukocytosis, neutrophilocytosis, increased ESR (p